1999
DOI: 10.1063/1.873528
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of laser penetration in overdense plasmas at relativistic intensities. II: Explosion of thin foils by laser driven fast electrons

Abstract: Propagation of a high-contrast frequency-doubled subpicosecond ͑300 fs͒ relativistic (I 2 up to 5ϫ10 18 W•cm Ϫ2•m 2 ) laser pulse through thin and initially solid foils is studied. Transmission values up to 10% are measured through targets with initial near solid densities. The strong intensity threshold observed for the transmitted energy is correlated with clear modifications of the transmitted and reflected spectra, electron generation, and beam imaging. Two-dimensional Cartesian particle-in-cell ͑PIC͒ simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Interaction of super-intense laser pulses with thin foils has been widely investigated during the past decade experimentally, [1][2][3][4] analytically, [5][6][7][8][9] and by computer simulations. [10][11][12][13][14] Many interesting physical phenomena have been predicted and observed experimentally in laser-foil interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction of super-intense laser pulses with thin foils has been widely investigated during the past decade experimentally, [1][2][3][4] analytically, [5][6][7][8][9] and by computer simulations. [10][11][12][13][14] Many interesting physical phenomena have been predicted and observed experimentally in laser-foil interactions.…”
Section: Introductionmentioning
confidence: 99%
“…ne=γnc [Fuchs et al, 1999] at normal incidence with γ being the Lorentz factor given by γ=(1+a0 2 ) 1/2 , with a0 2 =(posc/mc) 2 =Iλ 2 /(1.37×10 18 ), I being the laser intensity (in units of W/cm 2 ) and λ is the laser wavelength in microns.…”
Section: Laser Ion Acceleration Through the Laser Radiation Pressurementioning
confidence: 99%
“…Interactions of ultraintense laser pulses with thin foils have been investigated for nearly two decades [1][2][3][4][5]. Based on this body of research, various interesting physical phenomena have been predicted and observed in laser-foil interactions, such as the generation of high harmonics [6] and attosecond xray pulses [7,8], in addition to the formation of relativistic electron mirrors [9,10] and the acceleration of electrons and ions [11], among others.…”
Section: Introductionmentioning
confidence: 99%